Residual compressive strength of locally corroded intermediate tubular steel columns. (August 2022) - Kim, Young-Bae; Kamille Toledo, Kyra; Jeong, Young-Soo; Song, Si-Yun; Kim, In-Tae
Highlights: Residual compressive strength of intermediate tubular steel columns with local corrosion. Compressive loading test and finite element analysis of locally corroded columns. Correlation between the compressive strength and the degree of corrosion volume loss. Proposing a simple approach to evaluate the compressive strength using DOV. Abstract: Corrosion is a naturally occurring process in steel that can degrade the safety and durability of steel structures. Corrosion is inevitable; hence, the assessment of the load carrying capacity of corroded structural members is essential. In this study, compression tests and parametric finite element analysis were conducted on intermediate tubular steel columns to examine the effects of the degree of volume loss (DOV) of corrosion damage, and damage location along the column on the residual compressive strength. The results showed that the corrosion damage affects the compressive strength of the column and the reduction indicates a linear trend. However, the corrosion height does not affect the compressive strength when its value is greater than or equal to the half-wavelength of buckling. A simple approach with the DOV as a reduction factor is proposed to evaluate the compressive strength of locally corroded intermediate columns.